A seed coat-specific β-ketoacyl-CoA synthase, KCS12, is critical for preserving seed physical dormancy. Issue 3 (29th March 2021) - Chai, Maofeng; Queralta Castillo, Indira; Sonntag, Annika; Wang, Shixing; Zhao, Zhili; Liu, Wei; Du, Juan; Xie, Hongli; Liao, Fuqi; Yun, Jianfei; Jiang, Qingzhen; Sun, Juan; et al.
Abstract: Physical dormancy in seeds exists widely in seed plants and plays a vital role in maintaining natural seed banks. The outermost cuticle of the seed coat forms a water-impermeable layer, which is critical for establishing seed physical dormancy. We previously set up the legume plant Medicago truncatula as an excellent model for studying seed physical dormancy, and our studies revealed that a class II KNOTTED-like homeobox, KNOX4, is a transcription factor critical for controlling hardseededness. Here we report the function of a seed coat β-ketoacyl-CoA synthase, KCS12. The expression level of KCS12 is significantly downregulated in the knox4 mutant. The KCS12 gene is predominantly expressed in the seed coat, and seed development in the M. truncatula kcs12 mutant is altered. Further investigation demonstrated that kcs12 mutant seeds lost physical dormancy and were able to absorb water without scarification treatment. Chemical analysis revealed that concentrations of C24:0 lipid polyester monomers are significantly decreased in mutant seeds, indicating that KCS12 is an enzyme that controls the production of very long chain lipid species in the seed coat. A chromatin immunoprecipitation assay demonstrated that the expression of KCS12 in the seed coat is directly regulated by the KNOX4 transcription factor. These findings define a molecular mechanism by which KNOX4 and KCS12 control formation of the seed coat and seed physical dormancy. Abstract : Analysis of mutants in the model legume Medicago truncatula reveals a role for a seed coat fatty acid elongase complex subunit in seed physical dormancy.